Transforming Workforce Dynamics: The Role of Remote Work Flexibility, Technological Adoption, and Employee Wellbeing on Productivity of State Owned Enterprise Employee - Asriandi, Asriandi; Sitompul, Gabriel Amadeus; Sangaji, Joko (IJBLE Scientific Publications Community Inc., 2024)
This study examines the impact of remote work flexibility, technological adoption, and employee wellbeing on the productivity of employees in state-owned enterprises (SOEs). In response to shifting workplace dynamics, SOEs have increasingly implemented flexible work arrangements and digital tools, prompting the need to evaluate how these factors influence employee performance. Using a quantitative research approach, data were collected from 400 employees across various SOEs in Indonesia. The analysis, conducted using multiple linear regression, revealed that technological adoption significantly enhances employee productivity, followed by remote work flexibility and employee wellbeing. Findings also highlight challenges such as digital infrastructure limitations and the need for more comprehensive wellbeing programs. The study contributes to existing literature by providing insights into how SOEs can optimize workforce productivity through flexible work policies, digital transformation, and employee wellbeing initiatives. Practical recommendations for overcoming identified barriers are discussed, offering a roadmap for SOEs to enhance employee performance in a rapidly evolving work environment.